Tectonic transition from subduction to retreat of the palaeo-Pacific plate: new geochemical constraints from the late Mesozoic volcanic sequence in eastern Fujian Province, SE China. (24th June 2021) - Cao, Mingxuan; Zhao, Xilin; Xing, Guangfu; Fan, Feipeng; Yu, Minggang; Duan, Zheng; Chu, Pingli; Chen, Rong
Abstract: The widespread occurrence of late Mesozoic volcanic rocks in SE China is associated with widespread mineralization. Most geologists have accepted the model of Pacific plate subduction beneath the eastern Asian continent, but there are still controversies, especially the initial timing of the tectonic transition. In order to understand the tectonic evolution of the palaeo-Pacific plate subduction, an integrated study of zircon U–Pb, Lu–Hf isotope compositions and whole-rock geochemistry was carried out for Mesozoic volcanic rocks in eastern Fujian Province. According to the field observations and zircon U–Pb ages, these volcanic rocks can be divided into three phases: an early stage of Late Jurassic volcanic rocks (Phase 1, 159–153 Ma), a late stage of Late Jurassic volcanic rocks (Phase 2, 152–146 Ma) and an early stage of Early Cretaceous volcanic rocks (Phase 3, 143–139 Ma). Overall, these volcanic rocks are composed of intermediate–acid pyroclastic rocks and lava, with high SiO2, Na2 O, K2 O and Al2 O3 contents, belonging to the high-K calc-alkaline and peraluminous series, with enrichment in large ion lithophile and light rare earth elements but depletion in high-field-strength elements and heavy rare earth elements. However, the Phase 1 and 2 volcanic rocks contain different zircon Hf isotopic compositions and whole-rock geochemistry to the Phase 3 volcanic rocks, implying that they have a different petrogenesis. Our study combined with previous research shows that the decreasing zircon ϵ Hf ( t ) values of the Middle–Late Jurassic volcanic rocks indicate a decreasing mantle-derived material contribution. On the contrary, the majority of the Early Cretaceous volcanic rocks have variable ϵ Hf ( t ) values, requiring varied degrees of involvement of juvenile components in their origin. Thus, we consider that the Late Jurassic volcanic rocks were generated in a compressional tectonic environment during the early stage (> 146 Ma) of palaeo-Pacific subduction. In contrast, the Cretaceous volcanic rocks were formed in an extensional tectonic setting during a later stage (< 143 Ma) of subduction.